2021
DOI: 10.1016/j.ajem.2020.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between inpatient COVID-19 mortality and chest CT severity score

Abstract: Objectives There is scarce data available on the prognostic application of chest CT. The main purpose of this study was to evaluate the performance of a semi-quantitative CT severity score in identifying the risk of mortality in COVID-19 patients. Methods This retrospective cohort study was performed on 262 hospitalized COVID-19 patients. The CT severity score was assessed by two independent radiologists using a method previously used to score the severity of acute resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 9 publications
3
49
0
3
Order By: Relevance
“…Both left and right lung were divided into three zones including carina upper level, between the carina and inferior pulmonary vein, and below the inferior pulmonary vein level [ 6 , [41] , [42] , [43] ]. Then, we separately evaluated each zone involvement and scored between 0 and 4 (0: no involvement, 1: 1%-25% involved, 2: 26%-50% involved, 3: 51%-75% involved, and 4: 76%-100% involved) [ 6 , [41] , [42] , [43] , [44] , [45] , [46] ]. The total involvement score (Inv.Score) was calculated by summing up different zones scores.…”
Section: Methodsmentioning
confidence: 99%
“…Both left and right lung were divided into three zones including carina upper level, between the carina and inferior pulmonary vein, and below the inferior pulmonary vein level [ 6 , [41] , [42] , [43] ]. Then, we separately evaluated each zone involvement and scored between 0 and 4 (0: no involvement, 1: 1%-25% involved, 2: 26%-50% involved, 3: 51%-75% involved, and 4: 76%-100% involved) [ 6 , [41] , [42] , [43] , [44] , [45] , [46] ]. The total involvement score (Inv.Score) was calculated by summing up different zones scores.…”
Section: Methodsmentioning
confidence: 99%
“…The prognostic value of CT has been reported by several studies [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 ]. The use of a CT severity score (CT-SS) may be useful to standardize the assessment of lung alterations in COVID-19 pneumonia and to stratify patient risk and predict short-term outcomes [ 108 , 145 , 148 , 150 , 151 , 152 ].…”
Section: Chest Ctmentioning
confidence: 98%
“…Tabatabaei et al [ 148 ] reported that CT-SS is a reliable predictive factor of mortality in previously healthy non-elderly individuals with COVID-19 pneumonia. Abbasi et al [ 158 ] found a significant correlation between time of admission to time of death and CT-SS, and between CT-SS and time to ICU admission. These authors also found that mortality was significantly higher in patients with higher CT-SS, even after adjustments for clinical, demographic, and laboratory parameters.…”
Section: Chest Ctmentioning
confidence: 99%
“…As of March 19, 2021, 223 countries or regions were involved, more than 120.9 million confirmed cases were diagnosed, and these numbers have continued to increase [ 1 ]. The global mortality rate of COVID-19 is approximately 2.2% [ 1 ], while the mortality rate of hospitalized COVID-19 cases is commonly over 10.0% [ [2] , [3] , [4] ]. This is because hospitalized patients tend to have a more serious condition and generally require more effective and special therapies than those in isolation at home.…”
Section: Introductionmentioning
confidence: 99%
“…The Society of Cardiology [ 5 ] and the American College of Cardiology [ 6 ] strongly recommend careful cardiac assessment of symptomatic COVID-19 cases. Some primary studies also mentioned two potentially major cardiac risk factors that might be related to the severity of COVID-19 infection [ [2] , [3] , [4] ]. One risk factor is baseline cardiovascular disease (CVD), which is defined as a group of disorders of the heart and blood vessels, such as coronary heart disease, peripheral arterial disease, and congenital heart disease [ 7 ], occurring before COVID-19 infection and causing more serious clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%